Sustainable fish oil extraction from catfish visceral biomass: A comparative study between high-shear homogenization and high-frequency ultrasound on wet rendering process - Jaydeep Dave; Nishant Kumar; Ashutosh Upadhyay; Daniel Tua Purba; Tanaji Kudre; Pikunthong Nukthamna; Sampatee Sa-nguanpuag; Ali Muhammed Moula Ali; Sri Charan Bindu Bavisetty (My University, 2024)
Traditional wet rendering leads to the degradation of polyunsaturated fatty acids in fish oil. Therefore, we combined this method with high-shear homogenization and high-frequency ultrasound to extract oil from Clarias magur visceral biomass. This way, we aimed to achieve higher oil yield, shorter extraction times, and a better preservation of polyunsaturated fatty acids. High-shear homogenization and high-frequency ultrasound increased the oil yields by 9.17 and 10.55%, respectively, compared to traditional wet rendering. The oil quality was also improved, with lower acid and peroxide values. Scanning electron microscopy confirmed enhanced cell disruption for increasing the oil extraction efficiency. Fourier transfer infrared spectroscopy also proved the efficacy of homogenization and ultrasound pretreatment in enhancing the extraction of polyunsaturated fatty acids from C. magur visceral biomass. Their content showed a significant variation among different extraction methods. Specifically, the high-frequency ultrasound method resulted in a notable 15.1% increase, while the high-shear homogenization method demonstrated a significant 13.3% increase, compared to the wet rendering method (control). The oil extracted by the high-frequency ultrasound method demonstrated a 7.5% increase in eicosatetraenoic acid and a 11.7% increase in docosahexaenoic acid, as compared to the oil obtained from the control method. High-shear homogenization and high-frequency ultrasound shortened the extraction time and reduced the temperature requirements for oil extraction from wet biomass. These techniques have potential for efficient fish oil extraction, valuable in the healthcare and food industries.
Keywords: High frequency ultrasound; Homogenization; Meat and Animal Product Quality